Modern immunological approaches to assess malaria transmission and immunity and to diagnose plasmodial infection - C. T. Daniel-Ribeiro; J. Oliveira-Ferreira; M. F. Ferreira-da-Cruz (Memorias do Instituto Oswaldo Cruz, 1992)
The present paper reviews our recent data concerning the use of immunological methods employing monoclonal antibodies and synthetic peptides to study malaria transmission and immunity and to diagnose plasmodial infection. As concerns malaria transmission, we studied the main vectors of human malaria and the plasmodial species transmitted in endemic areas of Rondônia state, Brazil. The natural infection on anopheline was evaluated by immunoradiometric assay (IRMA) using monoclonal antibodies to an immunodominant sporozoite surface antigen (CS protein) demonstrated to be species specific. Our results showed that among six species of Anopheles found infected, An. darlingi was the main vector transmitting Plasmodium falciparum and P. vivax malaria in the immediate vicinity of houses. In order to assess the level of anti-CS antibodies we studied, by IRMA using the synthetic peptide corresponding to the repetitive epitope of the sporozoite CS protein, sera of individuals living in the same areas where the entomological survey has been performed. In this assay the prevalence of anti-CS antibodies was very low and did not reflect the malaria transmission rate in the studied areas. In relation to malaria diagnosis, a monoclonal antibody specific to an epitope of a 50 kDa exoantigen, the major component of supernatant collected at the time of schizont rupture, was used as a probe for the detection of P. falciparum antigens. This assay seemed to be more sensitive than parasitological examination for malaria diagnosis since it was able to detect plasmodial antigens in both symptomatic and asymtomatic individuals with negative thick blood smear at different intervals after a last parasitologically confirmed confirmed attack of malaria.